Multiple preputial stones: A case report and literature review. (2020) - Palinrungi, Muhammad Asykar; Kholis, Khoirul; Syahrir, Syakri; Syarif,; Faruk, Muhammad
Highlights: Preputial stones are a very rare form of urinary tract stone. Almost all the cases happen in a male in uncircumcised males, poor genital hygiene, low socioeconomic status, and phimosis. The symptoms and signs are due to phimosis. Neglected preputial stones can cause serious morbidities, such as hydronephrosis and renal failure. Abstract: Introduction: Preputial stones are a very rare form of urinary tract stone, and only small number cases have been reported in the literature, and tend to occur in uncircumcised males with poor genital hygiene, low socioeconomic status, and phimosis. Presentation of case: Here, we report a case in a male who presented with more than 100 preputial stones. The stones were evident on clinical examination by palpation on the preputial. The patient was treated by dorsal slit circumcision. Discussion: Preputial stones can occur at any age but are far more common in adult males. All cases of preputial stone are associated with severe phimosis in uncircumcised males. The symptoms and signs are due to phimosis, like in these patients, which causes urinary stasis beneath the foreskin. The stone is often palpable on examination of the prepuce, and a plain radiograph can confirm this. Neglected preputial stones can cause serious morbidities. Treatment involves the removal of stone and elimination of the predisposing cause. Conclusions: This case reminds us of the necessity of circumcision for adult uncircumcised males.